Soil mites (Acari) on plantations of chokeberry and black currant under microirrigation - Klimek, Andrzej; Rolbiecki, Stanisław (Biological Letters, 2010)
Bushes of black currant (Ribes nigrum) were slightly higher and wider, and their leaves had a higher content of major nutrients than chokeberry (Aronia melanocarpa). Soil samples were collected in 2004, in spring, summer and autumn, i.e. 3×20 samples from each experimental variant. Three irrigation variants were compared: no irrigation (C), drip irrigation (D), and micro-jet sprinkling (M). In the soil of the black currant plantation, the density of mites was higher (in variants C and D), as compared to the chokeberry plantation. The saprophagous oribatid mites were predominant in the studied mite communities, while Actinedida and Gamasida were less numerous. Oribatid mites were more numerous and more diverse in the black currant plantation than in the chokeberry plantation. The influence of irrigation on the density of oribatid mites was insignificant. In the communities of oribatid mites, Tectocepheus velatus was distinctly predominant on most plots.